Pedagang Etnis Tionghoa Lebih Suka Menonton Televisi dan Pedagang Etnis Batak Toba Lebih Suka Mendengarkan Musik: Kajian Tentang Penggunaan Waktu Luang Di Kota Tanjungpinang, Kepulauan Riau, Indonesia - Carlina Panjaitan; Rizabuana Ismail; Ria Manurung (Jurnal Empirika, 2016)
"Spare time" or "free time" is remaining time someone has besides the time they have for series of mandatory activities to make ends meet. Thus, spare time can be filled with activities such relaxing, resting, recreation, or any other activities to develop one's self without any coercion from others. With Torkildsen (2011) approach, in this writings we found out that Chinese ethnic merchants and Toba Bataknese ethnic merchants in Tanjung Pinang have different ways to spend their spare time: (1) On their time while doing the business, Chinese ethnic merchants prefer to fill their spare time watching television and on the other hand Toba Bataknese ethnic merchants prefer to spend their free time listening to the music. (2) As an activity, on their free time Chinese ethnic merchants choose to travel; Toba Bataknese ethnic merchants choose to do some exercises. (3) For positive mental health or for better mood, Chinese ethnic merchants choose to pay a visit to synagogues, while in contrary Toba Bataknese ethnic merchants prefer to attend "family-name gathering". (4) For broaden meaning of spare time, Chinese ethnics merchants prefer activities which give them freedom, while Toba Bataknese ethnic merchants choose to have conversations with colleagues. (5) From lifestyle perspective, both Chinese and Toba Bataknese ethnic merchants choose to fill their spare time with social activities.Â